For the Issue of the Sources of The Story of Barlaam and Ioasaph - Makaradze, Irma (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2022)
The issue of the authorship of the Greek text of The Story of Barlaam and Ioasaph has been a subject of great interest of medieval Studies scholars for many decades. The present article considers the sources used in the "Story of Barlaam and Ioasaph", on one hand and the author’s specificity while using these sources, on the other.